Інтродукція актинідії в Лісостепу України. Повідомлення 2. Особливості насіннєвого та вегетативного розмноження актинідії - Skripchenko, N.V.; Moroz, Р.А. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The article is devoted to investigation of the peculiarities of seeds and vegetative propagations of 5 species of Actinidia Lindl. genus under introduction in Forest-Steppe of Ukraine: A. kolomikta, A. arguta, A. purpurea, A. polygama and A. chinensis. Actinidia seeds lost their abilities to grow after first year of storage, what may be caused by the presence in it of high level of oil (33–35%), the majority of which are unsaturated fatty acids (98%). Optimum terms of actinidia propagation by wooded and semi-wooded roots are determined. The regenerate ability is species-specific feature and correlates with phytohormonal plant status. The phytohormonal balance ratio is the criteria of semi-wooded shoots ability for rooting. The efficiency of new growth-promoting factors was studied.